Cocaine-Levamisole Thrombotic Vasculopathy - Dy, Irene A.; Wiernik, Peter H. (Seminars in Thrombosis and Hemostasis, 2012)
The syndrome of cocaine-levamisole thrombotic vasculopathy is a tetrad of cutaneous manifestations, arthralgia, leukopenia, and positive antineutrophil cytoplasmic antigen (ANCA). Cocaine is cut with levamisole to potentiate its euphoric effects. However, along with this are the adverse reactions of levamisole such as fatal agranulocytosis, flu-like symptoms, and cutaneous thrombotic vasculopathy. High index of suspicion is needed for its diagnosis. This article will review on its toxicities, especially its prothrombotic effects.
Keywords: levamisole; cocaine; agranulocytosis; vasculitis; ANCA